The dialogues of Jeremiah: toward a phenomenology of exile - Modine, Mitchel (Gorgias dissertations, 2009)
This volume reads the diverse contents of Jeremiah as a kind of dialogue between competing perceptions of the exile. The author argues that coherence is to be found precisely in the incoherence, as it reflects the communal trauma of exile